Pedagogical Patterns of Grammatical Examples in Alfiyah Notebooks at an Indonesian Pesantren - Siti Sulaikho; M. Abdul Hamid; Umi Machmudah (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
This study analyzes the pedagogical patterns of grammatical examples recorded in students’ Alfiyah notebooks at an Indonesian pesantren. It responds to a gap between studies that discuss Arabic grammar teaching in general and the limited attention given to teacher-provided examples as micro-pedagogical input. This research employed a qualitative case study design with document analysis. The case was Special Female Class 3A at Madrasah Muallimin Muallimat, Bahrul Ulum Pesantren, Tambakberas, Jombang, involving 46 students from Classes 3-A1 and 3-A2 aged 16 to 17 years. The primary data consisted of students’ Arabic grammar notebooks containing examples presented by the teacher during Alfiyah instruction. Data were collected through documentation, repeated reading, unitization of examples, and classification based on lexical choice, lexico-grammatical arrangement, and Qur’anic verse use. The data were analyzed through qualitative content analysis, including coding, categorization, comparison across notebooks, and theoretical interpretation. The findings reveal three patterns: lexical repetition across different nahwu chapters, stable and simple lexico-grammatical arrangements in teacher-produced examples, and Qur’anic verses that were unfamiliar to students because they did not appear in the fiqh and hadith books studied during the same period. These patterns show that Alfiyah examples function as controlled pedagogical input that guides grammatical attention, reduces cognitive load, and connects grammar with authoritative texts. The study suggests that Alfiyah instruction requires staged examples that combine stability, lexical variation, structural expansion, and intertextual explanation